1982
DOI: 10.2337/diacare.5.4.386
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Subcutaneous Insulin Infusion in the Management of Painful Diabetic Neuropathy

Abstract: Nine patients with diabetic neuropathy were treated as outpatients with continuous subcutaneous insulin infusion (CSII). Painful symptoms were scored on a 10-cm horizontal graphic rating scale; motor conduction velocity (MCV) was measured in the median and peroneal nerves; and vibration perception threshold (VPT) was recorded in the great toes. All investigations were repeated after 6 wk and at the completion of 4 mo of CSII. Improved diabetic control was confirmed by significantly lower mean blood glucose lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
53
2
1

Year Published

1984
1984
2010
2010

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 202 publications
(64 citation statements)
references
References 15 publications
6
53
2
1
Order By: Relevance
“…However, that hyperglycemia may cause nervous functional changes in a short time has been shown by depressed pain threshold induced after intravenous glucose infusion over a few minutes," and by the symptomatic relief of painful diabetic neuropathy which has been achieved in 24 hours with insulin therapy. 28 Improvement of nerve function in long-standing diabetes is clearly related to blood glucose ~0 n t r o 1 .~~ Although no similar changes of heart rate were noticed in healthy subjects it should be stressed than only mild hyperglycemia was induced in them, as compared to the diabetic individuals. In order to induce similar glucose levels, a very large amount of intravenous solution would be necessary in nondiabetic subjects; this would increase the circulating volume and result in hemodynamic changes.…”
Section: Discussionmentioning
confidence: 97%
“…However, that hyperglycemia may cause nervous functional changes in a short time has been shown by depressed pain threshold induced after intravenous glucose infusion over a few minutes," and by the symptomatic relief of painful diabetic neuropathy which has been achieved in 24 hours with insulin therapy. 28 Improvement of nerve function in long-standing diabetes is clearly related to blood glucose ~0 n t r o 1 .~~ Although no similar changes of heart rate were noticed in healthy subjects it should be stressed than only mild hyperglycemia was induced in them, as compared to the diabetic individuals. In order to induce similar glucose levels, a very large amount of intravenous solution would be necessary in nondiabetic subjects; this would increase the circulating volume and result in hemodynamic changes.…”
Section: Discussionmentioning
confidence: 97%
“…There have been no comparable studies of autonomic function. The concept of direct metabolic damage to nerves by hyperglycaemia [5] is based on studies of motor nerve conduction velocity [15][16][17][18][19][20][21][22]. Yet it is sensory and autonomic nerve involvement, rather than damage to somatic motor fibres, which is responsible for the common and clinically serious manifestations of diabetic neuropathy [3,6].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study has reported that pain is a significant medical issue with a moderate-to-substantial impact on quality of life in some patients with diabetic neuropathy [19]. The prevalence of painful diabetic neuropathy (PDN) in diabetic patients is ranging from 11% of an insulin treated population [6] to 25% in a hospital diabetic clinic population [10]. However, the definition of PDN does not take in account that there are several types of peripheral nerve damage in diabetic patients that can present as painful neuropathies.…”
Section: Diabetic Neuropathymentioning
confidence: 99%